Exploring the expression patterns and clinical relevance of MED8 in pan-cancer and liver hepatocellular carcinoma: understanding tumor biology and prognostic significance - Wang, Shoulian; Yu, Jiwei; Pan, Chunpeng; Wang, Haibo; Niu, Qiguang (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examined the expression profiles and medical relevance of MED8 in various types of cancer specifically in liver hepatocellular carcinoma (LIHC). MED8, a subunit of the Mediator complex, plays a crucial role in gene expression regulation and has been implicated in various cellular processes and disease pathogenesis, particularly cancer. Through comprehensive analysis of multidimensional genomic and transcriptomic data from large-scale cancer databases, we examined the expression patterns of MED8 across different tissue types and cancer entities. Survival analysis showed the prognostic significance of MED8 expression in multiple cancer types. Additionally, we investigated the connections between MED8 levels and factors related to tumors, including microsatellite instability (MSI), tumor mutational burden (TMB), and cancer stem cell characteristics. Through gene set enrichment analysis (GSEA), enriched pathways and biological processes linked to MED8 expression were identified, providing insight into its functional significance in tumor biology. In the context of LIHC, we conducted a detailed analysis using the Xiantao platform, confirming the clinical significance of MED8 in LIHC and evaluating its diagnostic potential and utility as an independent prognostic marker. This research offers a comprehensive understanding of the diverse functions of MED8 in the field of cancer research, underscoring its significance as both a predictor of disease progression and a potential target for treatment in different types of cancer, particularly focusing on LIHC.